Na-Alginate Utilization of Brown Algae (Sargassum sp.) as A Halal Edible Film Basic Materials - Khasanah, Nisa Nur; Amalia, Vina; El Viera, Baiq Vera; Sawitri, Asti (UIN Sunan Gunung Djati Bandung, 2019)
Edible films made of Na-alginate from brown algae have great potential to be developed as brown algae have a fairly high abundance in Indonesia but have not been widely used. Therefore, in this study conducted by making edible films made from Na-alginate modified by the addition of hydrocolloids carrageenan and glycerol plasticizier. The addition of carrageenan biopolymers is the property of the produced Edible film. The use of glycerol as a plasticizer aims to improve the properties of elasticity Edible films. This research method consists of two stages. First, the isolation and characterization of Na-alginate. Both the preparation and characterization of making edible films. Na-alginate characterization results in yield of 25.68%, 10.84% moisture content, ash content of 23.79%. The carrageenan on the formula Edible films affect the characterization of the resulting films. The value of water absorption from 333.13% to 335.45% and the elongation of 26.26% to 33.34%, and the declining value of tensile strength of 8.93 MPa to 4.17 MPa and young's modulus values of 0.34 MPa to 0.22 MPa with the addition of carrageenan on an Edible film formula.